2015
DOI: 10.1038/srep10795
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical competence of ovariectomy-induced compromised bone after single or combined treatment with high-frequency loading and bisphosphonates

Abstract: Osteoporosis leads to increased bone fragility, thus effective approaches enhancing bone strength are needed. Hence, this study investigated the effect of single or combined application of high-frequency (HF) loading through whole body vibration (WBV) and alendronate (ALN) on the mechanical competence of ovariectomy-induced osteoporotic bone. Thirty-four female Wistar rats were ovariectomized (OVX) or sham-operated (shOVX) and divided into five groups: shOVX, OVX-shWBV, OVX-WBV, ALN-shWBV and ALN-WBV. (Sham)WB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…SMI is used to measure the rods and plates in the trabecular bone and gives information about the change in surface curvature that happens when a structure switches between an ideal plate-like to cylindrical or planar shape. In line with the results observed in this study, previous studies also indicate that in OVX rats, there is a trabeculae shift from a plate-like to a rod-like shape resulting in loss of trabecular connectivity and micro-architecture deterioration [ 66 , 67 ]. Furthermore, the treatment with ALN resulted in bone anabolic findings, mainly for Tb.Sp, Tb.N Tb.Pf, and SMI in the condyle.…”
Section: Discussionsupporting
confidence: 91%
“…SMI is used to measure the rods and plates in the trabecular bone and gives information about the change in surface curvature that happens when a structure switches between an ideal plate-like to cylindrical or planar shape. In line with the results observed in this study, previous studies also indicate that in OVX rats, there is a trabeculae shift from a plate-like to a rod-like shape resulting in loss of trabecular connectivity and micro-architecture deterioration [ 66 , 67 ]. Furthermore, the treatment with ALN resulted in bone anabolic findings, mainly for Tb.Sp, Tb.N Tb.Pf, and SMI in the condyle.…”
Section: Discussionsupporting
confidence: 91%
“…The OVX group showed deterioration in bone ductility compared to the sham-operated group. This result matched with previous study which reported that decreased oestrogen level via ovariectomy led to decreased in cortical bone strength [44]. There was an increasing trend of displacement value between the treated groups (OVX+V, OVX+T and OVX+VT) compared to the OVX group.…”
Section: Young Modulussupporting
confidence: 91%
“…RANKL secreted by osteoblasts promotes osteoclast differentiation 38 , and failure in osteoclastogenesis ameliorates bone formation 39 , meaning that the disruption of the activities of one of the two cell lineages always leads to the dysfunction of the other cell lineage. For example, the antiresorptive drug bisphosphonate also plays an inhibitory role in osteogenesis 40 , and anabolic agent PTH simultaneously promotes bone resorption 8 , both of which potentially risk aggravating osteoporosis, even leading to bone fracture; as a solution, combinative treatment is more effective in the enhancement of bone quality 41 . Therefore, the simultaneous antiresorptive and anabolic role of naringin shows great value in clinical disused osteoporosis treatment.…”
Section: Discussionmentioning
confidence: 99%